Harmony land: a board game to build awareness of inclusivity and preservation of Indonesian culture - Khoirun Nisa, Eka Lulu; Rahmawati, Putri Diana; Agung, Andi Ayesha; Syarif, Muhammad Haaziq Bujang; Hakiki, Imam (2025)
Harmony Land is an innovative educational board game designed as a medium for preserving Indonesian local wisdom values and raising awareness inclusivity issues. Different from conventional board games, Harmony Land presents content based on traditional houses from various regions in Indonesia as well as question cards that spark discussions about the values of inclusion for groups with special needs and indigenous peoples. This innovation was developed as a form of contribution to the goals of education and teaching as well as cultural preservation in line with the Tri Dharma values of higher education.